KEPEMIMPINAN VISIONER SEBAGAI KATALISATOR PENINGKATAN MUTU MANAJEMEN PENDIDIKAN DI SMP AL-WASHLIYAH 5 HAMPARAN PERAK - Ariana; Siahaan, Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Improving the quality of educational management is a strategic imperative in the face of dynamic social change and scientific advancements. In this context, visionary leadership is viewed as a key factor that serves as a catalyst for driving change and fostering continuous quality improvement. This study aims to analyze the role of visionary leadership as a catalyst in improving the quality of educational management. The research approach used is qualitative, employing data collection techniques such as observation, interviews, and documentation. The results indicate that visionary leadership plays a significant role in formulating clear policy directions, building a shared vision, and mobilizing all organizational components to enhance management effectiveness. Furthermore, visionary leadership is capable of creating a conducive organizational culture, improving human resource performance, and strengthening a management system that is adaptive to change. Thus, visionary leadership has proven to be the primary catalyst for the systematic and sustainable improvement of educational management quality